2012
DOI: 10.1124/mol.112.080036
|View full text |Cite
|
Sign up to set email alerts
|

Generation and Characterization of Novel Cytochrome P450 Cyp2c Gene Cluster Knockout and CYP2C9 Humanized Mouse Lines

Abstract: Compared with rodents and many other animal species, the human cytochrome P450 (P450) Cyp2c gene cluster varies significantly in the multiplicity of functional genes and in the substrate specificity of its enzymes. As a consequence, the use of wild-type animal models to predict the role of human CYP2C enzymes in drug metabolism and drug-drug interactions is limited. Within the human CYP2C cluster CYP2C9 is of particular importance, because it is one of the most abundant P450 enzymes in human liver, and it is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 32 publications
2
33
0
Order By: Relevance
“…However, in early clinical studies, the human value was found to be approximately of osimertinib in HLM was much greater than in MLM ( Figure 3A). To determine the reason for this species difference in metabolism, we analysed osimertinib stability in liver microsomes from Cyp2c, Cyp2d and Cyp3a gene cluster knockout mice, and from a combined Cyp2c/2d/3a triple-cluster knockout line (19)(20)(21)(22). Osimertinib stability was greatly increased in Cyp2d KO ( Figure 3A) and Cyp2c/2d/3a KO (not shown) microsomes but not in any of the other KO microsomes.…”
Section: Murine Cyp2d Are Responsible For the Species Difference In Omentioning
confidence: 99%
See 1 more Smart Citation
“…However, in early clinical studies, the human value was found to be approximately of osimertinib in HLM was much greater than in MLM ( Figure 3A). To determine the reason for this species difference in metabolism, we analysed osimertinib stability in liver microsomes from Cyp2c, Cyp2d and Cyp3a gene cluster knockout mice, and from a combined Cyp2c/2d/3a triple-cluster knockout line (19)(20)(21)(22). Osimertinib stability was greatly increased in Cyp2d KO ( Figure 3A) and Cyp2c/2d/3a KO (not shown) microsomes but not in any of the other KO microsomes.…”
Section: Murine Cyp2d Are Responsible For the Species Difference In Omentioning
confidence: 99%
“…The generation and characterisation of Cyp2cKO, Cyp2dKO, Cyp3aKO, Cyp2c/2d/3aKO, hCYP2D6*2 and hPXR/hCAR/hCYP3A4/3A7 mice has been described previously (19)(20)(21)(22). For the humanized lines, briefly, the hCYP2D6*2 line contains a targeted insertion of an expression cassette containing 9kb of the CYP2D6 promoter, along with all exons, introns and 5' and 3' untranslated regions, into the murine Cyp2d locus, from which all nine functional murine Cyp2d genes have been deleted (20).…”
Section: Animal Lines and Husbandrymentioning
confidence: 99%
“…Among these subfamilies, Cyp3a13 (Hasegawa et al, 2011) and Cyp2c44 (Scheer et al, 2012a) gene products were not studied because these genes were not deleted in the present KO mice. The latter is a well-known epoxygenase that deserves further study (Capdevila et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments with these new models (Cyp2c, Cyp2d, and Cyp3a KO mice) are clarifying the roles for enzyme families in the metabolism of xenobiotics. Presently, we used these three lines of KO mice to study two P450-related problems: (1) assessing possible mechanistic roles for CYP2C, CYP2D, and/or CYP3A subfamilies in the pain-relieving actions of morphine, and (2) , Taconic 9177-M) contain homozygous deletions of 14 full-length P450 genes (Cyp2c55, Cyp2c65, Cyp2c66, Cyp2c29, Cyp2c38, Cyp2c39, Cyp2c67, Cyp2c68, Cyp2c40, Cyp2c69, Cyp2c37, Cyp2c54, Cyp2c50, and Cyp2c70), but retain a functional Cyp2c44 (Scheer et al, 2012a). Cyp2d KOs [C57BL/6-Del(15Cyp2d22-Cyp2d26)1Arte, Taconic 9178-M] contain homozygous deletions of nine full-length P450 genes (Cyp2d22, Cyp2d11, Cyp2d10, Cyp2d9, Cyp2d12, Cyp2d34, Cyp2d13, Cyp2d40, and Cyp2d26) as recently described (Scheer et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…These mice are viable and healthy, although some animals exhibited liver inflammation. They also have significantly reduced metabolism of known CYP2C substrates such as tolbutamide (Scheer et al, 2012). Together, these models will be important for elucidating the roles of mouse CYPC enzymes in cardiovascular physiology and xenobiotic metabolism.…”
mentioning
confidence: 99%